Gay-straight alliances a handbook for students, educators, and parents - Macgillivray, Ian K. 1967- (Haworth series on GLBT youth & adolescence, 2007)
A step by step guide to the school club that provides a safe place for LGBT and straight kidsA Gay-Straight Alliance (GSA) provides a safe place for students to discuss issues, meet others, and get support from those who care. Gay-Straight Alliances: A Handbook for Students, Educators, and Parents explains exactly how to begin this important type of school club that helps build positive relationships and promotes knowledge and tolerance. This guide tells students what it takes to start a GSA at their school, teachers how best to work with GSAs, and helps principals and superintende.